2019
DOI: 10.3390/app9040678
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Irradiation-Induced Defect Engineering of Two-Dimensional 2H-MoS2 Few Layers

Abstract: Atom-thick two-dimensional materials usually possess unique properties compared to their bulk counterparts. Their properties are significantly affected by defects, which could be uncontrollably introduced by irradiation. The effects of electromagnetic irradiation and particle irradiation on 2H MoS 2 two-dimensional nanolayers are reviewed in this paper, covering heavy ions, protons, electrons, gamma rays, X-rays, ultraviolet light, terahertz, and infrared irradiation. Various defects in MoS 2 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 229 publications
(422 reference statements)
1
40
0
2
Order By: Relevance
“…Furthermore, they have emerged as a fascinating class of materials for catalysis . While irradiation of these materials with energetic (MeV) beams has been shown to modify their properties due to the creation of defects, here we demonstrated that irradiating bulk TMD flakes with a low energy proton flux leads to the formation and accumulation of hydrogen and enables the control of the electronic properties of ML TMDs at the nano‐ and micro scale through the creation of light‐emitting, highly strained domes. The irradiation process proposed here therefore allows the morphological and optical properties of the flakes to be altered without the creation of defects (as demonstrated by the stability of the domes, see Figure S11 in the Supporting Information, and by optical measurements, see Figure S15 in the Supporting Information), resulting into relatively large areas characterized by efficient light emission, due to the creation of the domes.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, they have emerged as a fascinating class of materials for catalysis . While irradiation of these materials with energetic (MeV) beams has been shown to modify their properties due to the creation of defects, here we demonstrated that irradiating bulk TMD flakes with a low energy proton flux leads to the formation and accumulation of hydrogen and enables the control of the electronic properties of ML TMDs at the nano‐ and micro scale through the creation of light‐emitting, highly strained domes. The irradiation process proposed here therefore allows the morphological and optical properties of the flakes to be altered without the creation of defects (as demonstrated by the stability of the domes, see Figure S11 in the Supporting Information, and by optical measurements, see Figure S15 in the Supporting Information), resulting into relatively large areas characterized by efficient light emission, due to the creation of the domes.…”
mentioning
confidence: 70%
“…The samples, consisting of thick (tens to hundreds of MLs) TMD flakes, were obtained by mechanical exfoliation, deposited on Si substrates, and afterwards proton‐irradiated using a Kaufman source (see the Experimental Methods). Differently from the other works in the literature concerning proton‐irradiation of TMDs—where beams with energies ≥10 5 eV are used, aiming at the controlled formation of defects in the irradiated samples—here we irradiate the flakes with low energy beams (≲20 eV), with the specific goal of suppressing the defect formation process. The top‐right inset of Figure a displays the optical microscopy image of a large bulk WS 2 sample after irradiation with an impinging dose d H = 8 × 10 16 protons cm −2 .…”
mentioning
confidence: 99%
“…The effect of ion and electron irradiation on the structural, 14 17 electronic 18 22 and optical 23 26 properties of 2D MoS 2 has been extensively researched. 27 Only a few studies have evaluated the effect of gamma irradiation on the physical properties of 2D group VI TMDCs. Using a 60 Co source, Felix et al irradiated 1 L WS 2 crystals with an absorbed dose of 400 Gy and observed ferromagnetic hysteresis, which they attributed to a defect configuration involving one W and two S vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 d,e showed the peak shifting of O 1s and Zr 3d core level towards higher binding energy, strong spin–orbit doublet of Zr 3d 5/2 -Zr 3d 3/2 obtained with splitting (δ 3d ) 2.37 eV and 2.32 eV for virgin and irradiated samples respectively as tabulated in Table 3 . The minor peak shifting (0.2 eV) of Zr 3d peak and significant peak shifting (1.4 eV) of O 1s spectra is observed as virgin sample is compared to the higher irradiated sample that might be due to the induced defects due to high energy irradiation 66 . The intensity of XPS peaks increased for the irradiated sample relative to the virgin sample.…”
Section: Resultsmentioning
confidence: 92%